Graduate students’ work status, perception, and online satisfaction predicting in-person instruction intention - Ayesha Calmerin Penuela; Ryan Michael F. Oducado (International Journal of Evaluation and Research in Education (IJERE), 2025)
Along with easing COVID-19 restrictions, schools are reopening and starting face-to-face classes. Intending in-person instruction after a relatively long period after off-campus and online learning requires exploration. This study determined the factors that predict students’ intention to attend in-person instruction among graduate students. The responses of 178 college of education graduate students were gathered electronically using valid and reliable survey instruments. Findings showed that graduate students are moderately to highly satisfied with online learning but also highly intend to attend in-person instruction. The majority of graduate students think that it is unsafe and possible to spread COVID-19, and felt worried to less worried when school reopens. Multiple regression revealed that work status, perceived safety and worry about school reopening, and online learning satisfaction predicted intention to attend in-person instruction. School administrators should ensure the safety operation of schools should students return to campuses, especially when there are threats to their health and security.